Violet in bloom a flower power book - Myracle, Lauren 1969- (Amulet Books, 2010)
Fifth-graders Katie-Rose, Violet, Milla, and Yasaman seem to have little in common except their flower-related names, but they nurture their new friendship through a social-networking site and a campaign to have healthier snacks served at school
Keywords: Best friends / Fiction; Friendship / Fiction; Schools / Fiction; Snack foods / Fiction; Natural foods / Fiction; Best friends / Juvenile fiction; Friendship / Juvenile fiction; Snack foods / Juvenile fiction; Natural foods / Juvenile fiction; California / Fiction; California / Juvenile fiction